Genetic Variation of Foxtail Millet (Setaria italica (L.) P. Beauv.) Germplasm From Polewali Mandar West Sulawesi Based On Morphological Characters - Ramlah Ramlah; Indrastuti Indrastuti; Mufti Hatur Rahmah; Marcia Bunga Pabendon (Universitas Sam Ratulangi, 2024)
Foxtail millet (Setaria italica (L.) P. Beauv.) is a cereal crop that has long been domesticated worldwide and has been adopted as a model crop to provide a deeper understanding of plant biology. This plant has long been a mainstay of indigenous Indonesian people, especially in Polewali Mandar, West Sulawesi Province. This study aims to evaluate the genetic variation of foxtail millet germplasm from Polewali Mandar, West Sulawesi based on morphological characters. Three germplasm populations were collected from Polewali Mandar to assess genetic variation in millet germplasm. The observations of morphological traits were carried out based on the IBPGR of Setaria italica. Genetic variation in foxtail millet populations was measured using 28 morphological traits with nine qualitative and 19 quantitative characters. The research showed that seed color, stem diameter, plant height, panicle stalk length, and panicle stalk diameter had diverse variations. Cluster analysis of morphological characters using the UPGMA method shows a similarity coefficient ranging from 0.15-0.2. At a genetic similarity coefficient of 0.2, the three populations were divided into Cluster A and Cluster B. Cluster A consists of two populations (Minna' and Lasse'). In contrast, Cluster B consists of one population (Bulawang). The millet population SLB.C.3-SLB.A.1 has the highest genetic distance and is a potential candidate to be selected as a parent cross to produce higher het-erosis. Intensification of millet plant breeding programs is expected to increase the genetic basis for determining specific characteristics.